METHODOLOGY OF TEACHING SPECIEL SCIENCES - Abdurasulov Farhod (Journals Park Publishing, 2022)
The article covers a short overview of the pedagogy of teaching special subjects. The article covers interactive techniques and the process of their application in practice.
Keywords: teaching; pedagogy; special education